If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2t + -4) = 48 + -6t Reorder the terms: 6(-4 + 2t) = 48 + -6t (-4 * 6 + 2t * 6) = 48 + -6t (-24 + 12t) = 48 + -6t Solving -24 + 12t = 48 + -6t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '6t' to each side of the equation. -24 + 12t + 6t = 48 + -6t + 6t Combine like terms: 12t + 6t = 18t -24 + 18t = 48 + -6t + 6t Combine like terms: -6t + 6t = 0 -24 + 18t = 48 + 0 -24 + 18t = 48 Add '24' to each side of the equation. -24 + 24 + 18t = 48 + 24 Combine like terms: -24 + 24 = 0 0 + 18t = 48 + 24 18t = 48 + 24 Combine like terms: 48 + 24 = 72 18t = 72 Divide each side by '18'. t = 4 Simplifying t = 4
| 4y-6x=16 | | 3(6y+5y)=2(-5+4y) | | 16=3q+4 | | -x-(-10)=-24 | | 3x^2+4x-420=0 | | 7f-9=3f-1 | | 7x-2x+x= | | 14n+15=-4n+17 | | 8x^3-9x^2=15x | | 6x+10+15x+2=7x | | 5x+12-3x-4=8x-25 | | -x+(-3)=13 | | 12x^2+16x-420=0 | | 9p+7=8p+11 | | 5x+3x+9x= | | y=w-at^3 | | ax+by+cz=d | | 5m^3+6mn+5m^2+6n=0 | | -0.10(18)+0.15x=0.05(x-8) | | 5x^2-20x+20=x^2 | | -4times-1+3= | | 6x+3ab=7x-7ab | | -4x-1+3= | | log[3](x)+7log[3](x^2)=14 | | 6x^2-6=5x | | 5(2t-1)+3(3t+4)=4(4t+7) | | 5m-8=m+4 | | 2Y-6X= | | 2r+48=6r-2r | | 3xy+5x+2+3y+x+4= | | 2r+55=4r+7 | | 2r+55=6r+7-2r |